ANALISIS SWOT DALAM MENINGKATKAN PENJUALAN PADA PERUSAHAAN PEMASARAN PRODUK CAP LANG DI KOTA MEDAN (STUDI KASUS PADA PT. DISTRINDO BINTANG AGUNG) - Rangkuti, sahnan; Antoro, Budi (PT. ANAN PUBLISHER CENDEKIA, 2025)
This study aims to analyze the marketing strategy of Cap Lang products through a SWOT analysis approach at PT. Distrindo Bintang Agung in Medan City. Cap Lang is widely recognized by the public as a traditional health product, yet it faces challenges in increasing sales amid intense market competition and shifting consumer preferences. This research employs a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that the company’s strengths lie in its well-established brand reputation and customer loyalty, while its weaknesses include limited utilization of digital platforms and lack of product innovation. Externally, opportunities include the growth of the health sector and increased public awareness of herbal products, whereas threats arise from competitive products and regulatory changes in distribution. The recommended strategy is the SO (Strengths-Opportunities) strategy, which emphasizes leveraging internal strengths to optimally seize external opportunities. Accordingly, PT. Distrindo Bintang Agung is expected to improve its marketing effectiveness and boost the sales performance of Cap Lang products in the Medan area.